O lazer sob a percepção de pessoas com deficiência usuárias de cadeiras de rodas - Cláudia Márcia Barbosa (2020)
This study aimed to verify whether people with disabilities who use a wheelchair have the same opportunity to participate and attend activities and leisure facilities available in the city of Belo Horizonte, compared to their peers, from their own perception. In addition, the study intended to make a survey of what is leisure for these subjects. The present study, of qualitative and quantitative character, is part of a larger research, which encompasses all the deficiencies. A questionnaire containing 126 questions was applied, divided into six blocks: Demographic Partner (SD); Family Composition (FC); Disabilities: Physical (DF), Auditory (DA), Visual (DV); Canadian Occupational Performance Measure (COPM); Participation Scale (EP); Leisure (L). For this investigation, the questionnaires (SD), (DF), (EP), (L) were analyzed. The study considered 126 people with physical disabilities who use wheelchairs, of both sexes (43% female and 57% male), with an average age of 49.8 years. In PE, the total scores of individuals in this sample were (n = 31) without significant restriction, (n = 44) severe restriction, (n = 26) moderate restriction, (n = 25) mild restriction. No individual with extreme restriction was identified. Leisure, for 90% of respondents, is related to the practice of an activity, whether it be social, sporting or cultural. Among the participants, the classification of these practices was established as follows: physical activities (n = 21); cultural activities - cinemas, museums, theaters, exhibitions: (n = 11); socio-cultural activities - television, bars, meetings for chatting, strolling in squares and parks: (n = 49); travel (n = 6); virtual activities (n = 64); no participation or no leisure (n = 5). It was possible to infer that the restriction levels are directly linked to the socio / economic level (income and education) of the individuals; their physical limitations; as well as poor transport conditions and poor accessibility in places suitable for leisure in the city. Personal and environmental factors influence the quality and satisfaction of leisure practices and, depending on the context, can be facilitators or barriers to access. It was possible to conclude that although Belo Horizonte is a city that offers various leisure spaces, people with disabilities encounter several barriers that contribute negatively to the realization of such practices. However, the impossibility of leisure is not only related to the personal conditions of the research participants, there is a portion of society's contribution that is not prepared to welcome people with disabilities who are wheelchair users. Thus, it is extremely important that public policies, providers of services and the community to develop mechanisms that identify intrapersonal and environmental factors that operate as a limiter in the social participation of people with disabilities. There is a gap in scientific production that covers the proposed theme.